Activation of HCN channels caused by elevated cAMP levels in periaqueductal gray promotes bone cancer pain. (January 2023) - Lei, Xiaolu; Yan, Yan; Zeng, Junwei; Wang, Rong; Li, Song; Xiao, Zhi; Liu, Xiaohong
Abstract: The periaqueductal gray (PAG) is an important relay center for the descending pathways that regulate nociceptive information transduction. Hyperpolarization-activated cyclic nucleotide-gated (HCN) channels play critical roles in the nerve injury-induced pain hypersensitivity. Previous studies have identified that HCN1 and HCN2 channel protein located in the ventral-lateral periaqueductal gray (vlPAG), a region important for pain regulation. However, it is not clear whether the HCN channel in vlPAG is involved in bone cancer pain (BCP). In this study, we assessed the role of HCN channels in BCP by measuring changes of HCN channel expression and activity in vlPAG neurons in bone cancer rats. In the present study, the BCP model was established by injecting SHZ-88 breast cancer cells into the right tibia bone marrow in rats. The mechanical withdrawal threshold (MWT) and thermal withdrawal latency (TWL) were measured to evaluate pain behavior in rats. HCN1 and HCN2 channels expression in vlPAG were detected by using Western Blot and immunohistochemistry. In addition, the cAMP level in vlPAG neurons was detected by ELISA, and HCN channel current (Ih ) of vlPAG neurons was recorded by whole cell patch-clamp to evaluate HCN channel activity. As a result, decreased MWT and TWL were observed in rats on 7d after SHZ-88 cell inoculation, and the allodynia was sustained until 21d after inoculation. At the same time, HCN1 and HCN2 channels expression and neuronal Ih in vlPAG were significantly increased in BCP rats. In addition, the level of cAMP in vlPAG also increased after SHZ-88 cell inoculation. Furthermore, intravlPAG injection of ZD7288 (HCN channels antagonist) could significantly reduce hyperalgesia and the elevation of cAMP in vlPAG in BCP rats. Our observations suggest that the elevation of cAMP may promote the activation of HCN channels in vlPAG in bone cancer rats, thereby promoting the development of bone cancer pain. Highlights: The study shows that activation of HCN channels caused by elevated cAMP levels in vlPAG promotes bone cancer pain.